Evaluation of the immature platelet fraction in the diagnosis and prognosis of childhood immune thrombocytopenia. (3rd October 2015) - Adly, Amira Abdel Moneam; Ragab, Iman Ahmed; Ismail, Eman Abdel Rahman; Farahat, Mona Mohammed
Abstract: Rapid assessment of platelet production would distinguish between thrombocytopenia due to decreased platelet production or increased peripheral platelet destruction. We evaluated the value of immature platelet fraction (IPF) in differentiating immune thrombocytopenia (ITP) from thrombocytopenia secondary to bone marrow failure and its potential use as a prognostic marker. Forty-one young patients with ITP were compared with 14 patients with hematological malignancies under chemotherapy, representing a control group with thrombocytopenia due to bone marrow suppression and 30 age- and sex-matched healthy controls. Patients were studied stressing on bleeding manifestations, organomegaly/lymphadenopathy and therapy. Complete blood count including IPF was performed using Sysmex XE-2100. ITP patients were classified into two subgroups: acute ITP with spontaneous resolution within 3 months from diagnosis and chronic ITP that lasted ≥1 year from diagnosis. Median IPF was 11.8% in patients with ITP, 7% in those with hematological malignancy and 3% in the control group ( p  < 0.001). ITP patients had significantly higher mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (P-LCR) and IPF compared with patients with malignancy or healthy controls, while plateletcrit (PCT) was significantly lower in ITP patients than other groups ( p  < 0.001). IPF was increased in patients with chronic ITP compared with acute ITP group ( p  < 0.001). Patients with active ITP had the highest IPF followed by those in partial remission, while ITP patients in remission had the lowest IPF. IPF was positively correlated to the number of lines of treatment used, MPV, PDW and P-LCR, while negatively correlated to platelet count and PCT among ITP patients ( p  < 0.001). Multiple regression analysis showed that platelet count and P-LCR were independently related to IPF. ROC curve analysis revealed that the cut-off value of IPF at 9.4% could be diagnostic for ITP patients with a sensitivity of 88% and a specificity of 85.7%. We suggest that IPF may be a rapid and inexpensive automated marker for etiology of thrombocytopenia and can be integrated as a standard parameter to evaluate the thrombopoietic state of the bone marrow. It may be considered as a potential prognostic marker for the development of chronic ITP.